The Social Gospel of pope John Paul II: A Guide to the Encyclicals of Human Work and the Authentic Development of Peoples - Biffi, Franco (1989)
Análisis de la encíclica pontificia Laborem exercens que aborda los problemas sociales del trabajo, la justicia y el desarrollo social.